The Innovative Role Of School Principals In Strengthening Islamic Values Through Digitally Based Education - Aji, Handaru Baskara; Kiram, Syaiful; Junaldi, Erik; Choirunisa, Mila Mutiara (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The rapid advancement of the digital era has presented both opportunities and challenges for educational institutions, particularly Islamic schools, in balancing technological competence with the preservation of spiritual and moral values. This study explores the innovative role of the principal of SD Islam Al-Azhar 17 Bintaro in strengthening Islamic values through the digitization of education. Employing a descriptive qualitative method, data were collected through interviews, observations, and documentation involving the principal and teachers as key informants. The findings reveal that the principal assumes multiple roles catalyst, creator, facilitator, and supervisor in integrating Islamic values into digital-based education. The principal’s strategies include the development of digital policies, provision of digital infrastructure, capacity building for teachers, and the formal integration of Islamic values into curriculum documents that harmonize the national, Al-Azhar, and Cambridge curricula. Furthermore, three flagship programs smart classroom, tahfidz, and bilingual education serve as platforms for embedding Islamic principles, reinforced by daily religious practices such as dhuha prayers, Qur’an recitation, and asmaul husna. These innovations demonstrate that curriculum digitization at SD Islam Al-Azhar 17 Bintaro goes beyond technical implementation, functioning as a substantive effort to internalize aqidah (faith), akhlaq (morality), and ibadah (worship) within both learning activities and school culture. The study concludes that innovative educational leadership is essential in creating a balance between technological mastery and Islamic character formation, thereby preparing students to become digitally competent, competitive, and morally upright individuals